Al-doped graphene-like BN nanosheet as a sensor for para-nitrophenol: DFT study - Peyghan, Ali Ahmadi; Noei, Maziar; Yourdkhani, Sirous (Superlattices and microstructures, 2013)
[Display omitted] •Sensitivity of pristine and Al-doped BN sheets to para-nitrophenol (p-NP) was studied.•p-NP adsorption on the pristine sheet is endothermic and unfavorable.•By Al-doping, the sheet becomes more reactive to p-NP.•Upon p-NP adsorption, Al-doped BN sheet becomes a p-type semiconductor.•Al-doped BN sheet might be potentially used in p-NP sensors. We investigated the electronic sensitivity of pristine and Al-doped BN sheets to para-nitrophenol (p-NP) by using density functional calculations. It was found that p-NP adsorption on the pristine sheet is endothermic and unfavorable. By replacing adsorbing boron atom of the sheet surface by an Al atom, the sheet becomes more reactive to p-NP, so energy of 20.4kcal/mol is released upon adsorption process. Upon p-NP adsorption on the Al-doped BN sheet, HOMO/LUMO energy gap of the sheet is dramatically decreased from 5.39 to 1.23eV and it becomes a p-type semiconductor. Thus, the Al-doped BN sheet may transform the presence of p-NP molecule into an electrical signal, and it might be potentially used in p-NP sensors.